P05.04 Intramedullary spinal cord tumours - a single centre ten year analysis. (19th September 2018) - Richards, O; Goacher, E; Derham, C
Abstract: Background: Intramedullary spinal cord tumours are relatively rare tumours of the central nervous system. Surgical outcomes are affected by many variables, including pre-operative neurological function, tumour histology and extent of resection. Emphasis remains on surgical treatment due to the limited adjunctive therapeutic options and poor drug penetration. Material and Methods: 49 patients were identified from a surgical database. Variables collected included pre-and post-operative Frankel Grade and Modified McCormick Scale assessments, tumour histology, extent of resection and length of follow up. Chi-Squared, Kaplan-Mier Survival and Mann-Whitney U-Tests were completed. Results: Ependymoma, Haemangioblastoma and Pilocytic Astrocytoma were the commonest tumour histologies. In total 21 different histological tumours were identified in the series. There was a statistically significant relationship between identification of the tumour plane and extent of resection (p<0.01), along with the extent of resection and recurrence (p<0.01). Compared to the other histological subtypes, ependymoma's demonstrated a significantly greater extent of resection (p=0.02). There was a significant relationship between the grade of tumour and progression free survival (p<0.01). We did not find a significant relationship between pre- and post-operative neurological function and survival. Conclusion: Tumour plane and the extent of tumour resection are significant determinants of progression free survival. Ependymoma, whilst being the commonest histology in our series were also the most resectable. Whilst complete resection reduces the rate of recurrence, tumour grade is the most important predictor of outcome.